Design And Implementation of Document Similarity Search System For WEB-Based Medical Journal Management - Mardi Siswo Utomo; Edi Winarko (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2011)
Abstract— Document similarity can be used as a reference for other information searches similar. So as to reduce the time-re-appointment for information following a similar document. Document similarity search capability is usually implemented on the features 'related articles'.Similarity of documents can be measured with a cosine, with preprosesing conducted prior to the document that will be measured. The indexing process and the measurement takes a relatively long excecution time. Problems with a web-based application to conduct the process and measuring the similarity index is a limited execution time, so the processing index and similarity measure in web-based application needs its own programming techniques.Problems with a web-based application to conduct the process and measuring the similarity index is a limited execution time, so the processing index and similarity measure in web-based application needs its own programming techniques.The purpose of this research is to design and create a software that give capability for web-based database management system of medical journals in Indonesian language to find other documents similar to the current document in reading at the time.The results of this research is the mechanism autoreload javascript and session cookies and can break down the process and measurement index similaritas into several small sections, so the process can be performed on web-based applications and the number of relatively large documents.Results with the cosine similarity measure in the case of Indonesian-language medical journal “Media medika Indonesiana” has a fairly high accuracy of 90%. Keywords— document similarity, cosine measure, web-based application.